A Love-Based Curriculum Model in Akidah Akhlak Education to Prevent Bullying - Muhammad Faiz Mujib; Dian Mohammad Hakim; Muhammad Fahmi Hidayatullah (Journal of Contemporary Islamic Education, 2026)
The prevalence of bullying in educational settings indicates that religious education has not yet fully succeeded in fostering empathetic and humanistic social relationships among students. This situation underscores the importance of an educational model that focuses not only on academic achievement and mastery of religious knowledge but also on strengthening character development and positive social interactions within the school environment. This study aims to describe the design, implementation, and model of the Love-Based Curriculum in Akidah Akhlak instruction to prevent bullying behavior at MTsN 3 Malang. This study employs a qualitative approach using a case study design involving the school principal, Akidah Akhlak teachers, the vice principal for curriculum, guidance counselors, and students as research subjects. Data were collected through interviews, observations, and documentation, then analyzed using a descriptive-interpretive approach. The results indicate that the Love-Based Curriculum is built through the integration of values such as compassion, empathy, respect for others, religious practices, teacher role modeling, and a humanistic school culture to support positive social interactions among students. The implementation of this model contributes to the development of moral awareness, harmonious interpersonal relationships, and the creation of a safer and more comfortable school environment, thereby helping to prevent bullying behavior. This study contributes to the development of humanistic and character-based Islamic education by emphasizing the importance of social relationships and emotional experiences in the educational process. These findings affirm that education grounded in the values of love and a humanistic approach can serve as an effective preventive strategy in reducing bullying behavior in school settings.